Spectrophotometric Study of the Complexation of Iodine and Iodine Monochloride with 1,4,7,-Trimethyl-1,4,7-Triazacyclononane in Chloroform Solution - Semnani, Abolfazl; Reza Pouretedal, Hamid; Reza Firooz, Ali (Asian Journal of Chemistry, 2010)
The interaction between iodine and iodine monochloride with 1,4,7-trimethyl-1,4,7-triazacyclononane (TMTACN) has been performed in chloroform solution at 25ºC. The results of iodine are indicative of the formation of [TMTACNI+I-3] through an equilibrium reaction. The stability constant of this reaction has been calculated from the absorbance-mole ratio data, using the nonlinear least square program "KlNFIT". In the case of iodine monochloride, the formation of polyhalide, 1 : 4 (as precipitate), 1 : 3 and 1 : 2 macrocyclic to iodine monochloride adducts are confIrmed. The formation of 1 : 2 complex was followed through an equilibrium reaction. However, the other adducts were formed through nonequilibrium reactions. The species of [TMTACNCl+I(ICl)n-], [TMTACNCl+(ICl)3-], [TMTACNCl+I(ICl)2-] and [TATMCl+I(IC)-] are suggested as the possible products.